Faktor Dominan Penghambat Pelaksanaan Proyek pada Industri Konstruksi - Adriadi, Adriadi; Namara, Idi; Zainuddin, Mairizal (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2026)
The construction sector in Indonesia has experienced significant growth in recent years, marked by frequent project delays across various construction projects. Project delays are a pressing issue in the Indonesian construction industry. Investors are increasingly concerned about this issue, necessitating a comprehensive study to uncover potential solutions. Therefore, a comprehensive study of construction project delays in Indonesia is needed. This study examines in-depth the parties involved in construction project implementation, namely project owners, consultants, and contractors. This study examines twenty (20) main factors causing project delays summarized from several leading journals in previous research from 2024-2016. These inhibiting factors are grouped into three main groups: Owners, Contractors, and Consultants. Literature research in previous journals was conducted to identify the inhibiting factors causing project delays. This analysis ranks project delays to identify the most dominant parties causing construction project delays. The results of this study found that all parties involved have the potential to be inhibitors and causes of delays, thus identifying and assessing the greatest potential causes of project delays. These findings are expected to be a guideline for proposing new strategies in implementing construction projects. Key words: Dominant Factors, Inhibitors of Project Implementation, Construction Industry